2014
DOI: 10.1021/ie501800j
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Modeling and Optimization of Batch Crystallization of Sugar Cane under Uncertainty

Abstract: This work presents a study on the agitation rate effects on the average diameter (% volume D(4,3)) in the batch crystallization of sugar cane in pilot-scale process. The mathematical model presented in this work includes the population balance equation (PBE), the mass and energy balances, and the kinetics equations of nucleation and growth rate. The kinetic parameters were calculated from optimization using experimental data obtained from a pilot-scale process. An uncertainty analysis was performed and used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…Each batch occurred in two hours, and samples were taken every fifteen minutes through the equipment probe to evaluate both FCM and D (4,3) through a Nikon Eclipse E200-LED Binocular microscope. The mathematical modeling was adapted to a model of a process in pilot scale-batch crystallization with cooling (using evaporation and cooling the solution)-as developed in [10]. The pilot scale process starts with approximately 752 cm 3 of syrup, operating for 40 min at 60 °C and is then cooled for 50 min to 40 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Each batch occurred in two hours, and samples were taken every fifteen minutes through the equipment probe to evaluate both FCM and D (4,3) through a Nikon Eclipse E200-LED Binocular microscope. The mathematical modeling was adapted to a model of a process in pilot scale-batch crystallization with cooling (using evaporation and cooling the solution)-as developed in [10]. The pilot scale process starts with approximately 752 cm 3 of syrup, operating for 40 min at 60 °C and is then cooled for 50 min to 40 °C.…”
Section: Methodsmentioning
confidence: 99%
“…7 Generally, optimal trajectory batch process profiles strongly depend on the constraints. From a review of the solutions that were obtained in several papers [14][15][16][17][18][21][22][23][24][25] , it can be concluded that the solution touch a constraint or several constraints during operation. In terms of state controllability, it could be dangerous to be near a constraint, as in the case of exothermic polymerization, in which a temperature constraint exists to prevent the polymer gel effect; if the process is disturbed, it could reach dangerous temperatures and produce a gel effect problem 9 .…”
Section: Trajectory Design As An Optimization Problemmentioning
confidence: 99%
“…Rackemann, Broadfoot, and Stephens () conducted a two‐dimensional (2D) modeling of natural circulation vacuum pans, although the 2D model cannot reach many details of sugar circulation in this process. Bolaños‐Reynoso, Sánchez‐Sánchez, Urrea‐García, and Ricardez‐Sandoval () conducted a study on optimizing the impeller speed to get the best diameter of sugar crystals. Ensinas, Nebra, Lozano, and Serra () using a thermoeconomic method to optimize the steam cost of the sugar factory.…”
Section: Introductionmentioning
confidence: 99%